Performance of the QuickVue Influenza A+B Rapid Test for Pandemic H1N1 (2009) Virus Infection in Adults - Poeppl, Wolfgang (Public Library of Science, 2011)
To investigate the diagnostic accuracy of the QuickVue® Influenza A+B rapid test we conducted a prospective observational study in which this rapid test was compared with a real-time reverse transcription polymerase chain reaction (RT-PCR) for pandemic influenza A H1N1 (2009) infection in Austrian adults. The sensitivity, specificity, and positive and negative predictive values of the QuickVue test compared with the RT-PCR were 26% (95% CI 18–35), 98% (95% CI 92–100), 94% (95% CI 80–99) and 50% (95% CI 42–58), respectively. The prevalence of pandemic H1N1 (2009) virus infection among the 209 patients included in the study was 57%. Our data suggest that a positive QuickVue test provides considerable information for the diagnosis of pandemic influenza A H1N1 (2009) virus infection in young adults but that a negative QuickVue test result should, if relevant for patient management or public health measures, be verified using PCR.